1999
DOI: 10.1038/sj.onc.1202927
|View full text |Cite
|
Sign up to set email alerts
|

Opposite transcriptional activity between the wild type c-myc gene coding for c-Myc1 and c-Myc2 proteins and c-Myc1 and c-Myc2 separately

Abstract: E-cadherin expression was previously shown to be activated by RB and c-myc speci®cally in epithelial cells, through interaction with the AP-2 transcription factor. Here we show that only a wild type c-myc gene, coding for the two c-Myc proteins c-Myc2 and c-Myc1, was able to transactivate the E-cadherin promoter, in contrast to c-Myc2 or c-Myc1 alone which strongly repressed E-cadherin in both epithelial cells and ®broblasts. In addition, overexpression of c-myc2 or cmyc1 inhibited c-myc and RB-mediated activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Consequently, in the BJAB cell line, LANA-mediated fold activation was likely less dramatic because of this already strong endogenous activation mediated by Myc. Similarly, HEK 293T expresses the SV40 T-antigen, a promiscuous transactivator that has been shown to activate the human Myc promoter (68). In fact, endogenous activation of the hTERT promoter was 10-fold higher in HEK 293T relative to HEK 293 by transient transfection luciferase assay, suggesting that endogenous hTERT promoter activity was indeed up-regulated in the HEK 293T cell line (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…Consequently, in the BJAB cell line, LANA-mediated fold activation was likely less dramatic because of this already strong endogenous activation mediated by Myc. Similarly, HEK 293T expresses the SV40 T-antigen, a promiscuous transactivator that has been shown to activate the human Myc promoter (68). In fact, endogenous activation of the hTERT promoter was 10-fold higher in HEK 293T relative to HEK 293 by transient transfection luciferase assay, suggesting that endogenous hTERT promoter activity was indeed up-regulated in the HEK 293T cell line (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…We provide here the first evidence that APC is a direct binding partner of AP-2␣, but several other AP-2␣-interacting proteins have been identified, including retinoblastoma protein (16,31), Myc (17,19), SV-40 large T antigen (32), human T-cell leukemia virus type 1 (33), PC4 (34), poly(ADP-ribose) polymerase (18), KLF9, and KLF12 (35,36). Many of these AP-2␣-binding proteins are well established regulators of gene expression.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, it has been indicated that over-expression of E2F3 or Ras induces tumor invasion through interaction with AP-2α, a characteristic TF in the caspases pathway, in epithelial cells of bladder cancer [28]. It has also been shown that c-Myc represses AP-2α trans -activation [29]. Another pathway found to be affected for more than one signature was the AhR pathway, which was found to be significant for both the Myc and Ras gene signatures.…”
Section: Resultsmentioning
confidence: 99%